Response Bias Modulates the Speech Motor System during Syllable Discrimination - Venezia, Jonathan H.; Saberi, Kourosh; Chubb, Charles; Hickock, Greg (Frontiers in Psychology, 2012)
Recent evidence suggests that the speech motor system may play a significant role in speech perception. Repetitive TMS applied to a speech region of premotor cortex impaired syllable identification, while stimulation of motor areas for different articulators selectively facilitated identification of phonemes relying on those articulators. However, in these experiments performance was not corrected for response bias. It is not currently known how response bias modulates activity in these networks. The present fMRI experiment was designed to produce specific, measureable changes in response bias in a speech perception task. Minimal consonant-vowel stimulus pairs were presented between volume acquisitions for same-different discrimination. Speech stimuli were embedded in Gaussian noise at the psychophysically determined threshold level. We manipulated bias by changing the ratio of same-to-different trials: 1:3, 1:2, 1:1, 2:1, 3:1. Ratios were blocked by run and subjects were cued to the upcoming ratio at the beginning of each run. The stimuli were physically identical across runs. Response bias (criterion, C) was measured in individual subjects for each ratio condition. Group mean bias varied in the expected direction. We predicted that activation in frontal but not temporal brain regions would co-vary with bias. Group level regression of bias scores on percent signal change revealed a fronto-parietal network of motor and sensory-motor brain regions that were sensitive to changes in response bias. We identified several pre- and post-central clusters in the left hemisphere that overlap well with TMS targets from the aforementioned studies. Importantly, activity in these regions covaried with response bias even while the perceptual targets remained constant. Thus, previous results suggesting that speech motor cortex participates directly in the perceptual analysis of speech should be called into question.